Response and assembly of abundant and rare taxa in Zaopei under different combination patterns of Daqu and pit mud: from microbial ecology to Baijiu brewing microecosystem - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Hanlan Tang; Qianglin Pan; Huifang Tang (Food Science and Human Wellness)
The quality and aroma of strong-flavor Baijiu are mainly dependent on Daqu, pit mud (PM), and the interaction of both. However, little is known about how their combination patterns affect the microbiome and metabolome of Zaopei, especially the metabolic function of rare taxa. Here, an experiment on industrial size was designed to assess the effects of 6 combinations (3 kinds of Daqu × 2 kinds of PM) on the composition and assembly of different taxa, as well as the flavor profile. The results showed that Zaopei’s microbiota was composed of a few abundant taxa and enormous rare taxa, and rare bacterial and abundant fungal subcommunities were significantly affected by combination patterns. The assembly processes of abundant/rare taxa and bacterial/fungal communities were distinct, and environmental changes mediated the balance between stochastic and deterministic processes in rare bacteria assembly. Furthermore, specific combination patterns improved the f lavor quality of Zaopei by enhancing the interspecies interaction, which was closely related to rare taxa, especially rare bacteria. These findings highlighted that rare bacteria might be the keystone in involving community interaction and maintaining metabolic function, which provided a scientific foundation for better understanding and regulating the brewing microbiota from the viewpoint of microbial ecology.